Assessing Tumor Oxygenation for Predicting Outcome in Radiation Oncology: A Review of Studies Correlating Tumor Hypoxic Status and Outcome in the Preclinical and Clinical Settings - Colliez, Florence; Gallez, Bernard; Jordan, Bénédicte F. (Frontiers in Oncology, 2017)
Tumor hypoxia is recognized as a limiting factor for the efficacy of radiotherapy by enhancing tumor radioresistance. It is strongly suggested that assessing tumor oxygenation could help to predict the outcome of cancer patients undergoing radiation therapy. Also, strategies have been developed to alleviate tumor hypoxia in order to radiosensitize tumors. In addition, oxygen mapping is critically needed for Intensity Modulated Radiation Therapy (IMRT), where the most hypoxic regions require higher radiation doses and the most oxygenated regions require lower radiation doses. However, the assessment of tumor oxygenation is not yet included in the day-to-day clinical practice. This is due to the lack of method able to map quantitatively and non-invasively tumor oxygenation. To fully integrate tumor hypoxia parameter into effective improvements of the individually-tailored radiation therapy protocols in cancer patients, methods allowing non-invasively repeated, safe and robust mapping of changes in tissue oxygenation are required. In this review, non-invasive methods dedicated at assessing tumor oxygenation with the ultimate goal of predicting outcome in radiation oncology are presented, including PET (Positron Emission Tomography) used with nitroimidazole tracers, MR (magnetic resonance) methods using endogenous contrasts (R1 and R2* based methods), and EPR (Electron Paramagnetic Resonance) oximetry; with the goal of highlighting results of studies establishing correlations between tumor hypoxic status and patients outcome in the preclinical and clinical settings.